Evaluation of the hematological and biochemical changes of blood profile in Arabian horses under the effect of training and pregnancy - Fathia M. Benashour; Fahima A. Alnagar; Nadia B. Gregni; Salheen M. Salheen; Amal O. Buker (المجلة الأفروآسيوية للبحث العلمي, 2024)
Knowing more information about Arabian horses raised in Libya is considered valuable before enrolling in any research on this category of horse's breed. This study investigated the influence of racing and pregnancy on the hematological and biochemical parameters. The blood samples were collected from 65 healthy Arabian horses in Libya for hematology and biochemistry analyses. The (WBC), (HB) and (HCT) were higher in racing and pregnant compared with (non-racing and non-pregnant) horses. The (MCV), (RDW-CV) was higher in pregnant than (non-racing and non-pregnant) horses. However, (MCHC) was significantly decreased in racing and pregnant animals. On the contrary, (MCH), (MPV), (PLT), (PDW) and (PCT) did not change among the examined Arabian horses. Biochemical analysis revealed a significant decrease in (ALT), (ALP), (AST) and (LDH), in racing and pregnant compared to the (non-racing and non-pregnant) horses with no significant different in AST. Although the (TP), and (IBIL) was significantly increased in race and pregnant compared to (non-racing and non-pregnant) horses, no changes were reported in (Alb), (T BIL), (D BIL) and (Glu) levels. The serum (TC) and (HDL) significantly decreased in racing and pregnant compared to non-pregnant animals with no significant change of the (TG), (VLDL), (LDL), (Cr) and urea of all animals. Finally, serum (P) and (K) were significantly lower, but (Mg) was significantly increased in racehorses and pregnant than non-pregnant mares and no changes were found in serum (Ca), (Na) and (Cl). It is crucial to understand these physiological changes to provide mares with the finest care and medical attention available. These data will help clinicians assess and care for pregnant mares appropriately.